Schedule-induced polydipsia in rats living in an operant environment - Petersen, Michael R. (1978)
The effect of variations in interreinforcement interval on the temporal and distributional relation between feeding and drinking was continuously monitored. Rats were housed continuously in an operant chamber in which water was freely available, but lever pressing was required to obtain food (45-mg pellets). Initially, pellets were delivered on a fixed-ratio 1 schedule of reinforcement, which was followed by testing on response-initiated fixed-interval 15-, 30-, and 60-second schedules. The total number of discrete, daily meals (a period in which several pellets were earned in succession) was slightly higher during the fixed-interval schedules than during the fixed-ratio 1, but there was no systematic effect of fixed-interval length on meal frequency. Total water consumption, in contrast, increased dramatically as the interval was lengthened: both subjects consumed two to three times as much water on the fixed-interval 60-second schedule as on the fixed-ratio 1. The increased water consumption was the result of an alteration in the distribution of drinking relative to eating. During the fixed-ratio 1 condition, drinking occurred infrequently following individual food pellets and represented the smallest percentage of total drinking; drinking occurred predominantly just before or after a meal. As the fixed interval was lengthened, however, the frequency of postpellet drinking gradually increased and eventually comprised the largest proportion of daily drinking.